: In vitro effect of crude extracts from eight Algerian steppe plants on mycelial growth and sporulation of Ascochyta pisi Lib. - Ammar Tiaiba, Malika Derbali & Boubekeur Seddik Bendahmane. (Anales de Biología (UNIVERSIDAD DE MURCIA), 2018)
Abstract: This work consists of studying the effect of crude extracts of eight plants growing in the Algerian steppe against Ascochyta pisi Lib., one of the members of the Ascochyta complex causing the Ascochyta blight of pea, with the aim of substituting them for chemical fungicides recognized for their harmfulness to the environment and public health. For this purpose, an in-vitro biocontrol test of the growth and sporulation of A. pisi was achieved by adding to its cultural medium a crude plant extracts or their sub-fractions. At the end of this trial, we found that the extracts of Artemisia alba Turra, Lycium arabicum Schweinf. Ex Boiss. and Peganum harmala Linn. recorded the best growth inhibition rates of pathogenic whereas, Artemisia campestris L. is more effective against its sporulation. Résumé : Ce travail consiste à étudier l’effet d’extraits bruts, de huit plantes poussant dans la steppe algérienne, contre Ascochyta pisi Lib., l’un des membres du complexe Ascochyta causant l’ascochytose du pois, dans le but de les substituer aux fongicides chimiques, connus pour leur nocivité à l’égard de l’environnement et la santé publique. A cet effet, des tests in-vitro de biocontrôle de la croissance et de la sporulation de A. pisi sont réalisés en additionnant au milieu de culture du champignons des extraits végétaux bruts ou de leurs sous-fractions. Au terme des essais, nous avons constaté que les meilleurs niveaux d’inhibition de la croissance du pathogène sont enregistrés avec les extraits de Artemisia alba Turra, Lycium arabicum Schweinf. Ex Boiss. et Peganum harmala Linn., alors que l’extrait de Artemisia campestris L. est plus efficace contre la sporulation. ملخص: يهدف هذا العمل من دراسة تأثير المستخلصات الخام لثمانية نباتات تنمو في السهوب الجزائرية ضد Ascochyta pisi Lib ، أحد أعضاء مجمع Ascochyta الذي يسبب مرض التبقع الاسكوكيتي على البازلاء ، بهدف استبدال المبيدات الفطرية الكيميائية المعروفة بأضرارها على البيئة والصحة العامة. لهذا الغرض ، تم إجراء اختبار للتحكم البيولوجي داخل المختبر لنمو وتكاثر A. pisi من خلال إضافة المستخلصات او جزيئاتها إلى وسط زرع الفطر. في نهاية هذه التجربة ، وجدنا أن مستخلصات Artemisia alba Turra ، .Lycium arabicum Schweinf. Ex Boiss و Peganum harmala Linn سجلت أفضل معدلات تثبيط نمو مسببات الأمراض ، في حين أن Artemisia campestris L. هو أكثر فعالية ضد إنتاج الأبواغ.
Plant extracts as biocontrol of Ascochyta blight of pea.
Keywords: Ascochyta blight, Pea, Growth inhibition, Sporulation, Steppe plants, Crude extract.Ascochytose, Pois, Inhibition de la croissance, Sporulation, Plantes steppique, Extraits bruts.التبقع الاسكوكيتي ، البازلاء ، تثبيط النمو ، إنتاج الأبواغ ، نباتات سهبية ، مستخلصات خامة.